Meningkatkan Keterampilan Passing Bawah pada Bolavoli Kelas IV SDN Sumberagung 2 dengan Metode Permainan Raja dan Pasukan - Gagas multigunindra; Susilaturochman Hendrawan K (Jurnal Multidisiplin Madani, 2022)
The purpose of this research is to improve the skill of passing down in volleyball in class IV SDN Sumberagung 2 Plosoklaten District, Kediri Regency. This research is a type of classroom action research with a qualitative descriptive approach. This classroom action research consists of 4 stages, namely (1) planning, (2) implementation, (3) observation. and (4) reflection. The subjects in this study were 13 fourth grade students at SDN Sumberagung 2, Plosoklaten District, Kediri Regency. The results showed in two cycles, namely three meetings in cycles 1 and 2. The success rate of students in cycle 1, meetings 1,2, and 3 was 38.6%, 43.3%, 49%, and in cycle 2 as much as 62%, 77%, 80%. In conclusion, using the king and troop game method can improve down passing skills in volleyball learning for fourth grade students at SDN Sumberagung 2.